ELEMENTAL CHARACTERIZATION OF COAL FLY ASH BY NEUTRON ACTIVATION ANALYSIS TOWARDS REFERENCE MATERIAL CERTIFICATION - Endah Damastuti; Woro Yatu Niken Syahfitri; Muhayatun Santoso; Natalia Adventini; Diah Dwiana Lestiani; Syukria Kurniawati (Badan Standardisasi Nasional, 2020)
Coal combustion by-products, such as coal fly ash, has known as a significant source of potentially toxic elements that may affect the environment since the increase of coal utilization as power fuel in Indonesia. Issuing the policies to protect the environment and public health is often based on analytical results. The quality of data analysis is very important since many crucial policies related to public health and environmental protections are based on the analytical results. Considering the need for reference material in ensuring the validity and reliability of the analytical results, reference material candidate of coal fly ash is being developed. Elemental characterization as one of the important parts in certifying the reference material is carried out using Neutron Activation Analysis (NAA) since it considered as high accuracy analytical method and commonly used to certified many reference materials throughout the world. Our NAA facility performance was assessed through optimizing analytical conditions by varying samples weight, method validation, and comparison test with other techniques as well. As much as 25, 100, and 250 mg of sample weight were assessed for its homogeneity effect. Method validation using SRM NIST 1633b had shown good results with bias not more than 10% compared to its certificate values. A comparison test with other results also showed a great agreement.